2013
DOI: 10.1016/j.bbalip.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Sugar availability modulates polyisoprenoid and phytosterol profiles in Arabidopsis thaliana hairy root culture

Abstract: Sugars are recognized as signaling molecules regulating the biosynthesis of secondary metabolites in plants. Here, a modulatory effect of sugars on dolichol and phytosterol profiles was noted in the hairy roots of Arabidopsis thaliana. Arabidopsis roots contain a complex dolichol mixture comprising three groups ('families') of dolichols differing in the chainlength. These dolichols, especially the longest ones are accompanied by considerable amounts of polyprenols of the same length. The spectrum of polyisopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…S1 and S2), suggesting dedicated roles of individual CPTs in plant responses to different stresses and implying a role of reactive oxygen species (ROS) signaling in Dol generation. Analysis of the content of Prens, a-unsaturated counterparts accompanying Dols in Arabidopsis hairy roots (Jozwiak et al, 2013), performed in parallel, revealed a modest decrease of their total content with the concomitant increase of Dols upon sorbitol treatment (Fig. 1).…”
Section: Dol Metabolism Upon Osmotic Stress: Biochemical Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…S1 and S2), suggesting dedicated roles of individual CPTs in plant responses to different stresses and implying a role of reactive oxygen species (ROS) signaling in Dol generation. Analysis of the content of Prens, a-unsaturated counterparts accompanying Dols in Arabidopsis hairy roots (Jozwiak et al, 2013), performed in parallel, revealed a modest decrease of their total content with the concomitant increase of Dols upon sorbitol treatment (Fig. 1).…”
Section: Dol Metabolism Upon Osmotic Stress: Biochemical Analysismentioning
confidence: 99%
“…The complexity of these mass spectra reflects the dispersion of the probability of formation of differentially labeled [ 13 C]Dol isotopomers/isotopologs (Skorupinska-Tudek et al, 2008). One should also note that, upon MS analysis, Dols form monovalent ions (z = 1); thus, the recorded m/z corresponds to the mass of the ion (Skorupinska-Tudek et al, 2003;Jozwiak et al, 2013). Moreover, the signal of each isotopomer (of a given m/z) in fact corresponds to various isotopologs (Dol ions containing the same number of 13 C atoms differently localized along the polyisoprenoid chain).…”
Section: Dol Metabolism Upon Osmotic Stress: Biochemical Analysismentioning
confidence: 99%
See 3 more Smart Citations